Everybody stacks: Lessons from household energy case studies to inform design principles for clean energy transitions. (June 2020) - Shankar, Anita V.; Quinn, Ashlinn K.; Dickinson, Katherine L.; Williams, Kendra N.; Masera, Omar; Charron, Dana; Jack, Darby; Hyman, Jasmine; Pillarisetti, Ajay; Bailis, Rob; Kumar, Praveen; Ruiz-Mercado, Ilse; et al.
Abstract: Stove stacking (concurrent use of multiple stoves and/or fuels) is a poorly quantified practice in regions with ongoing efforts to transition household energy to cleaner options. Using biomass-burning stoves alongside clean stoves undermines health and environmental goals. This review synthesizes stove stacking data gathered from eleven case studies of clean cooking programs in low- and middle-income country settings. Analyzed data are from ministry and program records, research studies, and informant interviews. Thematic analysis identifiedy key drivers of stove stacking behavior in each setting. Significant (28%–100%) stacking with traditional cooking methods was observed in all cases. Reasons for traditional fuel use included: costs of clean fuel; mismatches between cooking technologies and household needs; and unreliable fuel supply. National household surveys often focus on 'primary' cookstoves and miss stove stacking data. Thus more attention should be paid to discontinuation of traditional stove use, not solely adoption of cleaner stoves/fuels. Future energy policies and programs should acknowledge the realities of stacking and incorporate strategies at the design stage to transition away from polluting stoves/fuels. Seven principles for clean cooking program design and policy are presented, focused on a shift toward "cleaner stacking" that could yield household air pollution reductions approaching WHO targets. Highlights: Pervasive use of multiple stoves and fuels, or stove stacking, has been observed in numerous settings. Eleven implementation science case studies of clean cooking programs document extensive stacking. A cleaner stack can be achieved by promoting multi-component clean fuel interventions. Seven evidence-based design principles informing the ideal clean cooking stack are presented. Policy should focus on both increased uptake of clean cooking systems and discontinuation of polluting stoves and fuels.